Il silenzio di Lazzaro nel Carm. 80 di Cristoforo Mitileneo (Bisanzio e l'Occidente, 2021)
A poem by Christopher Mitylenaios praises Lazarus for his silence on what he saw during his stay in the afterworld. This paper frames Christopher’s poem within the various traditions about Lazarus’ ‘second earthly life’ and gives an explanation of the praise on the basis of Biblical parallels.
Keywords: Byzantine philology; Byzantine poetry; Christopher Mitylenaios